2014
DOI: 10.1371/journal.pone.0106599
|View full text |Cite
|
Sign up to set email alerts
|

Compliance of Disease Awareness Campaigns in Printed Dutch Media with National and International Regulatory Guidelines

Abstract: BackgroundThe European legislation prohibits prescription-only medicines' advertising but allows pharmaceutical companies to provide information to the public on health and diseases, provided there is no direct or indirect reference to a pharmaceutical product. Various forms of promotion have become increasingly common in Europe including “disease-oriented” campaigns.ObjectivesTo explore examples of disease awareness campaigns by pharmaceutical companies in the Netherlands, by assessing their compliance with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 14 publications
0
14
1
Order By: Relevance
“…Third, we could not evaluate the severity of overactive bladder because such information was unavailable in our data set. In addition, the limited data availability did not allow us to analyze the DTCI impacts on other patterns including total volume of prescriptions or adherence to treatment [ 5 7 ]. Therefore, further studies are needed to evaluate the impact of the DTCI campaign by incorporating these limitations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Third, we could not evaluate the severity of overactive bladder because such information was unavailable in our data set. In addition, the limited data availability did not allow us to analyze the DTCI impacts on other patterns including total volume of prescriptions or adherence to treatment [ 5 7 ]. Therefore, further studies are needed to evaluate the impact of the DTCI campaign by incorporating these limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Direct-to-consumer campaigns sponsored by the pharmaceutical industry, including direct-to-consumer advertising (DTCA) and direct-to-consumer information (DTCI) campaigns, have been a recent focus of prescription drug-use promotion in developed countries [ 1 – 4 ]. DTCA campaigns directly promote specific brand name medications, whereas DTCI campaigns are aimed at informing people about seeking healthcare services but should not directly promote specific drugs [ 4 – 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study from Leonardo Alves et al (2014) demonstrated that there is low compliance with self-regulation guidelines in the Netherlands. Even if their study was focused on the print media, the authors raised questions about the growing interest for online drug information and the importance of evaluating "the content and quality of disease awareness websites" to determine the effect on consumer behaviour (Leonardo Alves et al 2014: 8).…”
Section: The Impact Of Familiarizationmentioning
confidence: 99%